Tratamento a plasma de nanofibrilas de celulose para aplicação em compósitos - Silva, Bárbara Estefânia de Almeida (2017)
The application of cellulose nanofibrils to the production of composites has been studied and presents promising results, mainly due to the abundance of the material, which is of a renewable source, and to its low cost. However, the presence of the hydroxyl groups in their chain and their storage in aqueous solutions limits their application as reinforcement in nonpolar matrix composites. In this context, this work aimed to modify the wettability and adhesion properties of films of cellulose nanofibrils to apolar matrices, through plasma treatment. For this, nanocellulose films with thickness of 38 ? 8 ?m were produced by the casting method, from a suspension of nanofibrils in water. The atomic force microscopy characterization (AFM) of the suspended nanofibrils indicated that most of them have an average diameter of less than 75 nm. Each film obtained, after drying the suspension, was then cut into 13 samples with 2 x 1 cm, 12 of which were exposed to plasma and one stored as untreated. Three films were treated with oxygen plasma, with excitation power of 150 W, for 30 minutes and pressure of 0.1, 0.3 and 0.5 Torr. Another three films were treated with sulfur hexafluoride plasma at pressures of 0.1, 0.2 and 0.3 Torr, with a power of 150 W for 15 minutes. It was observed that weight loss was greater than 40% for the films treated with the most extreme conditions oxygen and sulfur hexafluoride. The results also showed that the treatments with sulfur hexafluoride promoted the reduction of the receptivity of the samples to the liquids, with contact angles of approximately 60º for water and 50º for diiodomethane. The profilometry technique revealed that the roughness of the films varied after the treatment with oxygen and sulfur hexafluoride, but the high error bars impede a definitive conclusion on the tendency of these variations. The X-ray diffraction analysis (XRD) indicated no significant change in the crystallinity of the samples with the treatments. In the Fourier Transform Infrared absorption spectra (FTIR), a C-F bonding related peak appeared for the 0.3 Torr sulfur hexafluoride treated sample, indicating the presence of fluorine in that sample. The scanning electron microscopy (SEM) allowed the visualization of the changes in the topography of the films, due to the etching processes resulting from the action of the plasma and the films ruptures caused by the high removal of surface material. In order to test the incorporation of treated films into composites using polyolefins as the matrix, polyethylene pellets were solubilized in xylene for the production of composite films. The treated and untreated nanocellulose films were placed in Petri dish jointly to the polyethylene films still dissolved and left at room temperature. After drying, adhesion between the films was tested through the adhesive tape test, resulting in class-zero adherence, according to the technical standard. It is believed that the lack of adhesion is a result of the composite production method that should be optimized for future work, in order to provide a better investigation of the effects of plasma on the surface properties of the film of cellulose nanofibrils.